Adoption Process for Reporting Solutions in a Large Enterprise - Kliueva, Tatiana (2025)
The growing availability of data and the abundance of business intelligence (BI) tools on the market have made the implementation of reporting solutions a routine part of business activity in large organizations. However, the adoption of these reporting products remains a significant challenge (Wang, 2014). Often it falls into a “grey” zone where BI departments focus on the technical implementation process and business users are reluctant to communicate adoption barriers. This thesis focuses on this significant problem of the evaluation of reporting products adoption process within large enterprises. The main goal of this master's thesis is to evaluate the process of reporting solutions adoption in a large enterprise and provide recommendations for improving the process. Through a multi-faceted approach, it analyzes the interplay between company environment, user characteristics, and the implementation process. The adoption of reporting products is a comprehensive multi-stage process (Puklavec et al., 2018). The thesis describes the individual phases of the adoption journey – from the initial awareness phase, through the evaluation, testing, and implementation phases, to the integration phase, in which the products are incorporated into the company's processes and infrastructure.The company environment has a big impact on reporting process, specifically company maturity in analytical, data, and IT domains (Bothe, 2022) and decision-making culture (Popovic et al., 2012). Based on these insights, the thesis adopts and validates a framework for evaluating the adoption of reporting solutions. The framework integrates BI‑team assessments, usage statistics, and user feedback into a continuous evaluation cycle designed to support improvements across BI strategy, report development practices, monitoring and evaluation, and organizational initiatives.